2017
DOI: 10.1249/mss.0000000000001296
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Interval Training, Appetite, and Reward Value of Food in the Obese

Abstract: This study suggests that chronic HIIT has no independent effect on appetite or food reward when compared with an isocaloric program of MICT in obese individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 28 publications
3
69
0
4
Order By: Relevance
“…Another possible confounding factor might have been the compensatory eating responses to exercise protocols that were not accounted for during the intervention, with possible implications on glycaemic control. There is a lack of consensus in the literature regarding the impact of HIIT on appetite regulation, with some studies suggesting a beneficial impact, while others showed no impact …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible confounding factor might have been the compensatory eating responses to exercise protocols that were not accounted for during the intervention, with possible implications on glycaemic control. There is a lack of consensus in the literature regarding the impact of HIIT on appetite regulation, with some studies suggesting a beneficial impact, while others showed no impact …”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of consensus in the literature regarding the impact of HIIT on appetite regulation, with some studies suggesting a beneficial impact, 30 while others showed no impact. 31 When addressing the issue of which type of exercise led to greater improvements in glycaemic control (HIIT vs MCT), there is no experimental evidence to support that HIIT led to superior results in individuals with type 2 diabetes. 6 The proposed mechanisms mediating improvements in glycaemic control suggest that exercise can improve muscle-insulin sensitivity and post-exercise glucose disposal by enhancing the delivery and transport of glucose across muscular tissue, while also improving intromyocellular metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, our recent systematic review on weight management interventions found limited evidence on the impact of exercise interventions on food reward [6••]. Among the included studies, two investigated the impact of highintensity interval exercise compared with either moderateintensity interval training [53] or continuous training [60]. Using a cross-over design, Alkahtani et al [53] found that in response to acute exercise after a 4-week exercise intervention, liking for high-fat savory food seemed to increase after MIIT and decrease after HIIT in men with overweight or obesity (interaction p = 0.09).…”
Section: Chronic Exercise Training Studiesmentioning
confidence: 99%
“…Adding support to the notion that changes in body fat are key to changes in appetite hormones, one study showed that greater weight loss in response to highintensity interval training was associated with greater post-training increases in fasting acylated ghrelin [68]. Martins et al [68] did not, nevertheless, find these relationships with concentrations of 12 appetite-related hormones after exercise training that could be modulated by the body fat of participants. In these studies, efforts should be made to define adiposity status with precise body fat percentage measures alongside BMI.…”
Section: Chronic Exercisementioning
confidence: 97%
“…This body of work suggests that exercise training increases fasting hunger and postprandial satiety [40,68], and may improve the coupling between energy intake and energy expenditure in response to food intake [12,40,42] . This study similarly demonstrated that energy intake in the 24 hours after consumption of the high energy preload was lower post-training but was unchanged in response to exercise when the low energy preload was consumed.…”
Section: Chronic Exercisementioning
confidence: 99%